Perfil metabólico de cordeiros Santa Inês terminados em confinamento - Libardi, Keli Daiane Cristina (2014)
The objective of this study was to evaluate levels of food restriction followed by refeeding on the metabolic profile of lambs finished in feedlot. For this purpose, 24 male sheep were used at 20 kg body weight in a randomized and four restriction levels (0, 20, 40 and 60%) and 6 replicates per treatment design. The experiment was divided into two distinct periods of 64 days each, at the first call restriction, the rats were assigned to treatments: no restriction (ad libtum consumption remains at 10%), restriction of 20, 40 and 60% compared to consumption of the control treatment. In the second period, called the period of refeeding, food was offered ad libtum to all animals in the experiment. The variables of the metabolic profile (protein, energy, mineral and enzyme) at the beginning and end of feed restriction and the end of the intake were evaluated. For the evaluation of blood metabolites of the metabolic profile in animals, commercial laboratory kits were used. Data were analyzed using the F test of analysis of variance, when detected significant differences, regression analysis was used to study the levels of food restriction, and Tukey test for comparison between samples. In the absence of treatment effect averages relating to treatments 20, 40 and 60% restriction were calculated in the three collection periods. All statistical procedures were evaluated at 5% probability by SISVAR (2003) statistical program. It was observed that phosphorus levels were lower in animals to start the period of feed restriction, the same occurring for concentrations of urea, glucose and magnesium, which were adversely affected with the increase in the level of restriction imposed. Already in the final stages of food restriction there was a linear decrease for biochemical concentrations of urea, glucose and phosphorus; contrary, cholesterol concentrations increased linearly at the end of the period. The end of food restriction on the initiation of the restriction, negatively influenced the concentrations of triglycerides, glucose and creatinine, unlike the values of total protein, albumin, urea and cholesterol showed a significant increase with the final restrictive period. Already on feedback, there was decreasing for urea, glucose and magnesium linear behavior. In the second trial, it was found that the concentrations of total protein, globulin, total cholesterol, glucose, creatinine and phosphorus showed differences (P <0.05) between collection periods. The levels of food restriction affect protein metabolism and also interfered in the energy and mineral metabolism, and feedback resulted in changes in protein and energy metabolism